2012
DOI: 10.1089/thy.2011.0312
|View full text |Cite
|
Sign up to set email alerts
|

American Thyroid Association Consensus Review and Statement Regarding the Anatomy, Terminology, and Rationale for Lateral Neck Dissection in Differentiated Thyroid Cancer

Abstract: Lateral neck lymph nodes are a significant consideration in the surgical management of patients with DTC. When current guidelines formulated by the ATA and by other international medical societies are followed, initial evaluation of the DTC patient with ultrasound (or other modalities when indicated) will help to identify lateral neck lymph nodes of concern. These findings should be addressed using fine-needle aspiration biopsy. A comprehensive neck dissection of at least nodal levels IIa, III, IV, and Vb shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(177 citation statements)
references
References 62 publications
4
167
3
3
Order By: Relevance
“…Cervical LNM in PTC have been identified as an independent risk factor for regional recurrence 4, 5, 6, 7, and emerging evidences from large population‐based studies have indicated decreased disease‐free survival rate and increased mortality associated with regional LNM 7, 8, 9, 10. There is universal agreement that therapeutic lateral neck dissection (LND) should be undertaken in patients with PTC and clinically lateral LNM (LLNM) on the basis of palpation or imaging examination 11, 12. However, determining the appropriate extent of LND remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical LNM in PTC have been identified as an independent risk factor for regional recurrence 4, 5, 6, 7, and emerging evidences from large population‐based studies have indicated decreased disease‐free survival rate and increased mortality associated with regional LNM 7, 8, 9, 10. There is universal agreement that therapeutic lateral neck dissection (LND) should be undertaken in patients with PTC and clinically lateral LNM (LLNM) on the basis of palpation or imaging examination 11, 12. However, determining the appropriate extent of LND remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…47 In terms of the surgical approach to regional nodes, a compartment-orientated neck dissection is recommended for all patients with metastatic disease. 48 If this involves the central neck, bilateral levels VI and VII should be dissected. If the lateral neck is also involved, dissection of levels IIa, III, IV, and V is recommended in a "comprehensive neck dissection.…”
Section: Approach To Therapymentioning
confidence: 99%
“…1). 59) In the absence of significant lymphadenopathy at levels IIa, III, IV and Vb, disease above the spinal accessory nerve (IIb or Va) or in level I is uncommon.…”
Section: Lateral Neck Dissectionmentioning
confidence: 99%
“…Therefore, the ATA recommended a comprehensive selective neck dissection of levels IIa, III, IV, and Vb. 59) In comparison with the central compartment, the lateral neck harbors lower rates (23%) 60) of occult metastasis and elective surgery results in higher postoperative complication rates. Despite this, some experts continue to advocate selective prophylactic lateral neck dissection.…”
Section: Lateral Neck Dissectionmentioning
confidence: 99%